Cytomorphological Spectrums in Tuberculous Lymphadenitis: Understanding the Stages of Disease - Pradhan, Anju; Poudyal, P.; Upadhyaya, P.; Pokhrel, S. (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Tuberculous lymphadenitis is the most common form of extrapulmonary tuberculosis and one of the main causes of lymphadenopathy. Fine Needle Aspiration Cytology (FNAC) has played a substantial role in diagnosis of tuberculous lymphadenopathy and it has become a first-line diagnostic technique. The aim of this study was to describe and understand the spectrum of cytomorphological changes seen in tuberculous lymphadenitis corresponding to stages of disease and to associate the cytomorphological changes with Acid Fast Bacilli (AFB) positivity. Methods: This is a retrospective cytomorphological study of cytologically diagnosed tuberculous lymphadenitis. The recorded details of clinical presentation and site of the lymph nodes were noted. The slides were stained with Papanicolaou, Giemsa and AFB. Result: There were a total of 203 cases with age ranging from 3- 75 years. Four cytomorphological patterns observed were Necrotising Granulomatous Lymphadenitis (NGL; 45.32%), Granulomatous Lymphadenitis (GL, 18.22%), Necrotising Suppurative Lymphadenitis (NSL; 21.18%) and Necrotising Lymphadenitis (NL; 15.27%). Necrotising patterns were observed in immunocompromised individuals like HIV infected patients, in patients with previous history of tuberculosis and in patients with chronic renal disease. Strong AFB positivity was observed in necrotising patterns. Lymph nodes of head and neck region were the most common site of involvement with cervical being the commonest. Conclusion: Necrotizing patterns are observed in the later stages of disease or in the immunocompromised patients. Strong positivity for AFB is observed in the smears with necrotizing patterns and less in the granulomatous pattern.